A Collocation Method for Solving Fractional Order Linear System - Refahi Sheikhani, Amir Hosein; Mashoof, Mahamad (Journal of the Indonesian Mathematical Society, 2017)
In this paper we propose the collocation method to achieve the numerical solution of fractional order linear systems where a Fractional Derivative is defined in the Caputo sense.We use Taylor collocation method, which is based on collocation method for solving fractional differential equation. This method is based on first taking the truncated Taylor expansions of the vector function’s solution in the Fractional order linear system and then substituting their matrix forms into the system. Using collocation points, we have a system of linear algebraic equation.The method has been tested by some numerical examples. DOI : http://dx.doi.org/10.22342/jims.23.1.257.